2020
DOI: 10.1177/0145561320957759
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Intramuscular Hemangioma (Infiltrating Angiolipoma) of the Lower Lip: A Case Report and Review of the Literature

Abstract: Objective: To report a case of a recurrent intramuscular hemangioma (IMH) of the lower lip of a 68-year-old female and review the published literature to provide an overview of the presentation, diagnostic strategy, pathological classification, and management of these lesions within the oral cavity. Methods: A case report was conducted by reviewing the documentation at a single institution. A systematic literature review on OVID MEDLINE and PubMed was performed using the MESH terms “intramuscular hemangioma” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
0
9
0
6
Order By: Relevance
“…We instituted excision biopsy in toto to provide a better functional outcome. It is reported that inadequate excision leads to a recurrence rate between 20% and 60% [ 2 , 26 , 46 , 47 ]. No recurrence was reported in our case in the past 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We instituted excision biopsy in toto to provide a better functional outcome. It is reported that inadequate excision leads to a recurrence rate between 20% and 60% [ 2 , 26 , 46 , 47 ]. No recurrence was reported in our case in the past 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we performed open synovectomy to provide a better functional outcome. The literature stated that inadequate excision poses a recurrence rate of 20–60% [ 33 , 34 , 35 , 36 ]. No recurrence was reported in our case in the last 8 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas, although being the most common benign tumor, arising within skeletal muscle account for less than 1% of all hemangiomas and occur in large musculature of the trunk and extremities 1 , 2 . Intramuscular hemangiomas are uncommon in the head and neck region (14–21% of intramuscular hemangiomas) and mostly involve the masseter muscle 1 3 . Intramuscular hemangiomas are nonencapsulated benign neoplasms involving skeletal muscle and deep peripheral soft tissue that are composed of vascular channels along with adipose tissue, fibrous, and myxoid tissue 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Intramuscular hemangiomas are uncommon in the head and neck region (14–21% of intramuscular hemangiomas) and mostly involve the masseter muscle 1 3 . Intramuscular hemangiomas are nonencapsulated benign neoplasms involving skeletal muscle and deep peripheral soft tissue that are composed of vascular channels along with adipose tissue, fibrous, and myxoid tissue 2 , 3 . Intramuscular hemangiomas occur mostly in childhood with 85% noted by the age of 1 year 4 , 5 with no sex preference 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%